Surrealismo e Américas (Caligrama: Revista de Estudos Românicos, 2011)
Palavras-chave: Resenha; Robert Ponge; Nara H. N. Machado; Surrealismo e Novo Mundo.Keywords: Review; Robert Ponge; Nara H. N. Machado; Surrealismo e Novo Mundo.